2021
DOI: 10.9770/jesi.2021.8.4(3)
|View full text |Cite
|
Sign up to set email alerts
|

Give or buy contexts and internet experience as a factor differentiating of readiness to provide different types of personal data in m-commerce

Abstract: Studies show that privacy concerns are an important factor in m-commerce and m-buyers are often not ready to disclose private data to m-shops. An e-questionnaire survey was used to gather opinions in three groupsca. 160 Poles, ca.160 Ukrainians and ca.130 Romanians, to study decisions of potential consumers concerning disclosure of personal data when downloading paid or free mobile applications in 3 different contexts: downloading an attractive app to their smartphone as a gift, as a promo purchase, or from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Perceived risk (PR), as citizens' subjective expectation of suffering a loss in pursuit of the desired outcome [18], is an important predictor of citizens' e-government adoption [4,6,15,19,20], as well as a crucial factor in m-commerce that influences user's use behaviour [21]. Regarding e-government, perceived risk is composed of the perception of exposure of personal information, privacy, and the loss of money.…”
Section: Hypothesis 2 (H2) Toi Positively Influences Citizens' E-government Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived risk (PR), as citizens' subjective expectation of suffering a loss in pursuit of the desired outcome [18], is an important predictor of citizens' e-government adoption [4,6,15,19,20], as well as a crucial factor in m-commerce that influences user's use behaviour [21]. Regarding e-government, perceived risk is composed of the perception of exposure of personal information, privacy, and the loss of money.…”
Section: Hypothesis 2 (H2) Toi Positively Influences Citizens' E-government Adoptionmentioning
confidence: 99%
“…EE was measured with four items, PE was measured with three items, SI was measured with three items, and FC was measured with three items, which were borrowed and modified from the existing literature [1,23,26,27]. Egovernment adoption (EGA) was supported by three items [21,40] and represents citizens' intention to inquire for information, complete transactions, and share opinions through e-government websites. Table 1 shows all constructs and items.…”
Section: Measurementmentioning
confidence: 99%
“…Studies show that companies that carry out mcommerce activity are also very concerned about ensuring confidentiality when customers are not ready to disclose private data [68,87]. Thus, several factors have been identified that can influence the decisions of potential consumers to make their data available [73,87,88].…”
Section: Security and Privacy In M-commercementioning
confidence: 99%
“…The mobile site has adequate security features SP1 [36,40,68,69,73,87,88] This mobile site protects information about my card SP2 I trust the mobile site to keep my personal information safe SP3 It protects information about my mobile-shopping behavior SP4…”
Section: Conceptual Model Developmentmentioning
confidence: 99%